2015
DOI: 10.1039/c5cp00313j
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemisorbed hydroxyl species in alkaline electrocatalysis of glycerol on gold

Abstract: The mechanism of energy conversion in a direct glycerol fuel cell (DGFC) is governed by the anode supported heterogeneous steps of glycerol electro-oxidation. In aerated alkaline electrolytes, glycerol also participates in a base catalyzed process, which can release certain species mixing with the anode catalyzed surface products. As a result, selective probing of the surface catalytic reactions involving such systems can be difficult. The present work addresses this issue for a gold anode by using the analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 71 publications
0
32
0
2
Order By: Relevance
“…The second peak corresponds to the glycerol oxidation which is presented in the literature by different authors [14][15][16][17][18][19][20][21][22]. In general, the catalytic activity for glycerol oxidation is observed with Pt, Cu, and Au electrodes.…”
Section: Experimental Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…The second peak corresponds to the glycerol oxidation which is presented in the literature by different authors [14][15][16][17][18][19][20][21][22]. In general, the catalytic activity for glycerol oxidation is observed with Pt, Cu, and Au electrodes.…”
Section: Experimental Methodsmentioning
confidence: 94%
“…in the study of Ureta [18], the mechanism of alcohol oxidation in alkaline media on a gold electrode was investigated and it is suggested that the optimal oxidation for alcohols is at pH 11. Also, Shi [19] studied the kinetics of low concentration of glycerol in alkaline media using voltammetry on a gold foil. Recently, Qi [20] studied the generation of tartronade during glycerol oxidation in alkaline media, using an AuC coated electrode.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, neither the OH − ion (proton acceptor) coverage nor its role on EOG mechanism or kinetics under different electrochemical conditions have been explored in atomic detail. Partly controversial results regarding the mechanism have been published and it has remained unresolved whether Au(OH) ads catalyzes the dissociation of a C-H bond 48,49 or an O-H bond 2,18,19,24 and whether primary or secondary O-H/C-H bonds are more reactive on the Au surface. 22,50 It has also remained unresolved if chemical steps, such as keto-enol tautomerism between DHA and GLD identified for thermochemical glycerol oxidation, 51,52 are important in EOG and whether this depends on the pH.…”
Section: Introductionmentioning
confidence: 99%
“…The first peak corresponds to a typical sudden increase in Energy Storage Technologies for off-grid Houses 71 | B a c k u p 3 oxidation upon reducing gold from its oxidized state in alkaline media. The second peak corresponds to the glycerol oxidation which is presented in the literature by different authors [96][97][98][99][100][101][102][103][104].…”
Section: Analysis Of Catalyst For Glycerol Oxidationmentioning
confidence: 99%
“…in the study of Ureta [100], the mechanism of alcohol oxidation in alkaline media on a gold electrode was investigated and it is suggested that the optimal oxidation for alcohols is at pH 11. Also, Shi [101] studied the kinetics of low concentration of glycerol in alkaline media using voltammetry on a gold foil. Recently, Qi [102] studied the generation of tartronade during glycerol oxidation in alkaline media, using an AuC coated electrode.…”
Section: Introductionmentioning
confidence: 99%